2016
DOI: 10.5603/piap.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

Low DLCO in Idiopathic Pulmonary Arterial Hypertension—Clinical Correlates and Prognostic Significance

Abstract: Introduction: Decreased diffusing capacity of the lung for carbon monoxide (DLCO) is observed in some idiopathic pulmonary arterial hypertension (IPAH) patients, but its clinical significance is uncertain. We aimed to assess clinical correlates and prognostic significance of low DLCO in IPAH patients. Material and methods:In the group of 65 IPAH patients the cut off value for low DLCO was set up based on histogram as < 55% of predicted value. Demographic data, exercise capacity, lung function tests, hemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…found an increased mortality in idiopathic PAH patients with an DLCO <55% predicted. 21 Kang et al. described a low DLCO as poor prognostic factor in patients with PAH associated with connective tissue disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found an increased mortality in idiopathic PAH patients with an DLCO <55% predicted. 21 Kang et al. described a low DLCO as poor prognostic factor in patients with PAH associated with connective tissue disease.…”
Section: Discussionmentioning
confidence: 99%
“…20 Szturmowicz et al found an increased mortality in idiopathic PAH patients with an DLCO <55% predicted. 21 Kang et al described a low DLCO as poor prognostic factor in patients with PAH associated with connective tissue disease. 22 Hoeper et al found a significantly worse survival rate in patients with PH due to heart failure with preserved ejection fraction and DLCO <45% predicted.…”
Section: Dlco As Prognostic Parameter In Phmentioning
confidence: 99%
“…A particular focus of the study was the subgroup of patients with severe DLCO reduction, because reduced DLCO has been associated with lower oxygen saturation 19 and a greater likelihood of death in PAH. [13][14][15][16] In a retrospective study of Group 1 PAH patients (n ¼ 408), the risk of death was approximately 2.4 times greater for patients with DLCO values in the lowest tertile for the study population. 14 Kaplan-Meier estimates of survival in patients with (A) normal or mild DLCO reduction (≥60% of predicted), (B) moderate DLCO reduction (40% to o60% of predicted), and (C) severe DLCO reduction (o40% of predicted), according to supplemental oxygen usage.…”
Section: Discussionmentioning
confidence: 99%
“…idiopathic PAH (n ¼ 65), DLCO of o55% of predicted was associated with a 4-fold greater risk of death within 5 years. 15 Reduced DLCO has also been shown to predict mortality in patients with pulmonary hypertension, resulting from heart failure with preserved ejection fraction. 20,21 Among patients in the severe DLCO reduction subgroup in our study, there was less disparity in prognostic factors and measures of disease severity than in the overall population.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation